Bororo Fulani Pastoralists and Yoruba Farmers’ Conflicts in the Upper Ogun River, Oyo State Nigeria, 1986–2004 (2015)
This article, based on in-depth oral interviews, focuses on the conflicts between Bororo Fulani pastoralists and Yoruba farmers in Saki and Iseyin towns of the Upper Ogun River (Oke-Ogun), Oyo State Nigeria to show the power disparity and competition over land resources. The conflicts that occurred between Bororo Fulani pastoralists and Yoruba farmers are classified as: economic (crop destruction and cattle killing); social (murder, rape, armed banditry, molestation on both sides of the conflict); and communal (large-scale destruction of villages, pastoral settlements and markets). Other conflicts involved access to grazing and water resources and access to markets. These conflicts were products of resource scarcity and broader challenges of power relations between indigenes and settlers/migrants in Nigeria. Ethnicity became more conspicuous among local people as these conflicts intensified. This article discusses the intervention of Yoruba traditional rulers (Oba) and Fulani headman (Ardo) in the formation of peace committees in Iseyin and Saki towns.